Dynamic physiology and transcriptomics revealed the alleviation effect of melatonin on Reaumuria trigyna under continuous alkaline salt stress - Li, Xuebo; Wang, Lei; Wang, Heyi; Hao, Rui; Gao, Lunkai; Cui, Hongbo; Wu, Hai; Wu, Xiaodong; Qiao, Tong; Bai, Weijie; Zhang, Liming (Frontiers in Plant Science, 2025)
IntroductionReaumuria trigyna, a pivotal salt-tolerant plant species in Central Asian salt desert ecosystems, has garnered significant attention due to its resilience under harsh environmental conditions. This study investigates the response mechanisms of melatonin on the dynamic physiology and transcriptomics of Reaumuria trigyna, a critical salt-tolerant plant species in Central Asian salt desert ecosystems. Despite significant progress in understanding plant salt tolerance, research on the positive effects of melatonin on Reaumuria trigyna, particularly its impact on seed germination and the underlying physiological and molecular mechanisms, remains limited.MethodsIn this study, we evaluated the physiological responses of Reaumuria trigyna under continuous alkaline salt stress and examined the effect of melatonin on seed germination.ResultsOur results demonstrate that melatonin at concentrations of 300μmol/L significantly enhances plant growth and promotes the accumulation of osmotic regulators. Notably, melatonin treatment increased the germination rate by 35.48% compared to the alkaline salt stress group, which exhibited a 52.15% lower germination rate than the untreated control. The key mechanism identified involves melatonin’s ability to increase antioxidant enzyme activity, reduce reactive oxygen species and hydrogen peroxide levels, and alter gene expression patterns.DiscussionTranscriptomic analysis revealed significant changes in gene expression, particularly in photosynthetic signal transduction, phytohormone signaling, MAPK signaling, and the peroxisome pathway, which are crucial for the plant’s response to alkaline salt stress. Our findings provide new insights into how melatonin affects plant growth, salt tolerance, seed germination, and gene expression in Reaumuria trigyna under continuous alkaline salt stress. These results address a significant gap in current scientific knowledge and offer valuable theoretical support and practical guidance for cultivating salt-resistant crops and the ecological restoration of salt-affected desert environments.